Validation of environmental disinfection efficiency of traditional Ayurvedic fumigation practices - Bhatwalkar, Sushma Bagde (J Ayurveda Integr Med, 2019)
Environmental disinfection greatly reduces the occurrence of nosocomial or healthcare associated infections (HCAIs) which are the major healthcare problems worldwide. In India, Ayurvedic traditional fumigation with natural plant products is used to disinfect environment. In the present study, environmental disinfection efficiency of traditional fumigation practice has been evaluated by using natural plant products such as garlic (Allium sativum) peel, turmeric (Curcuma longa) powder, Carom (Trachyspermum ammi) seeds (Ajwain) and Loban (resin of Styrax benzoin and Boswellia species). The efficiency of traditional fumigation using these natural products to disinfect air and surface was evaluated. The effect of traditional fumigation on the microbiological quality of air was revealed by active air sampling. In addition, the ability of the traditional fumigation using garlic peel to disinfect inanimate surface was evaluated using three strains of methicillin resistant Staphylococcus aureus (MRSA). Glass slide was artificially contaminated with the bacteria and fumigated whereas non-fumigated slide served as control. The control and fumigated slides were analyzed for surviving bacteria and subjected to scanning electron microscopy (SEM) analysis. Traditional fumigation performed separately with three grams of garlic peel, turmeric, carom seeds and loban powder reduced the average air borne bacterial colony forming units (cfu)/m(3) compared to non-fumigated control. The SEM analysis showed reduced number of bacteria in garlic peel fumigated surface samples. The results of the study strongly suggested that the traditional Ayurvedic fumigation with natural plant products is effective in reducing air-borne bacteria and in disinfecting inanimate surfaces. The traditional fumigation with herbal products has huge potential to address the problem of nosocomial infections.